Co-application of sheep manure and commercial organic fertilizer enhances plant productivity and soil quality in alpine mining areas - Yu, Zhongyang; Yao, Xixi; Yang, Mingchun; Hu, Shengbin; An, Xiaoting; Li, Changhui (Frontiers in Microbiology, 2024)
Background and aimsThe addition of organic fertilizers and sheep slat manure have important effects on soil quality in alpine mining areas, but how they affect soil physicochemical properties and microorganisms is not yet known.MethodsThe current study employed field-controlled experiments and high-throughput sequencing technology to investigate differences in soil physicochemical properties, microbial community structures, and diversity under four treatments: no fertilization (CK), 100% sheep manure (SM), a combination of 50% sheep manure and 50% commercial organic fertilizer (MF), and 100% commercial organic fertilizer (OF).ResultsAboveground biomass increased by 191.93, 253.22, and 133.32% under SM, MF and OF treatments, respectively, when compared to CK treatment. The MF treatment resulted in significantly higher soil total nitrogen, total phosphorus, organic matter, and available nitrogen content compared to other treatments. Soil total nitrogen content, total phosphorus content, organic matter, available nitrogen content and available phosphorus content were 211, 120, 380, 557, and 271% higher, respectively, under the MF treatment than the CK treatment. Different nutrient additions significantly influenced soil microbial community composition. The SM and MF treatments notably increased soil bacterial and fungal community Operational Taxonomic Units (OTUs) indices and Chao 1 indices, while nutrient addition had no meaningful effect on the Simpson indices for microbial communities. There was a highly significant positive correlation between aboveground biomass and observed soil nutrient content.ConclusionThe combined application of sheep manure and commercial organic fertilizer is more conducive to improving soil quality and enhancing plant productivity in alpine mining areas.